A mechanistic review on immunomodulatory effects of selective type two cannabinoid receptor β‐caryophyllene. (1st June 2022) - Baradaran Rahimi, Vafa; Askari, Vahid Reza
Abstract: β‐Caryophyllene (BCP) is a plant‐derived compound and occurs naturally in various foods and spices, including cinnamon, citrus, fruits, clove, curry, and pepper. BCP showed different pharmacological effects, such as antioxidant and antimicrobial properties. This article tried to gather updated knowledge of the anti‐inflammatory, antioxidant, and immunomodulatory effects of BCP and searched using various databases and appropriate keywords until April 2022. Several studies showed that the anti‐inflammatory effects of BCP are mainly provided through cannabinoid receptor 2 (CB2 ) receptor activation and the peroxisome proliferator‐activated receptor (PPAR) γ pathway. It has also been demonstrated that BCP suppresses both protein and mRNA expression levels of interleukin (IL)‐6 and reduces relevant proinflammatory cytokines but increases the anti‐inflammatory cytokine IL‐13. Previous results indicated that the antioxidant effects of β‐caryophyllene were suggested through different pathways, including activation of nuclear factor erythroid 2‐related factor‐2 (Nrf2)/heme oxygenase‐1 (HO‐1)/antioxidant axis and inhibition of the HMG‐CoA reductase activity, and oxidative stress biomarkers levels. Furthermore, various results showed immunomodulatory effects of BCP through inhibiting microglial cells, CD 4+ and CD 8+ T lymphocytes, modulated Th1 /Treg immune balance through the activation of the CB2 receptor, and reducing mitogen‐activated protein kinases (p38MAPK) and NF‐kB activation and increased ionized calcium‐binding adaptor molecule‐1 (Iba‐1) and IL‐1β.